Opportunities And Threats In Online Business: The Perspectives Of Entrepreneurs And Consumers - Simanjuntak, Amoi Sanyo; Cecylia, Cecylia; Korri Juita Situmorang; Mei Wanita Simanjuntak; Rahmat Fadhiil; Wilda Noveliana Tambunan; Freddy Johanis Rumambi (SEAN Institute, 2024)
This study aims to analyze the opportunities and threats in online business from the perspectives of entrepreneurs and consumers. In the rapidly growing digital era, online business has become a primary alternative for many entrepreneurs to reach a global market. This research employs a qualitative approach with in-depth interviews of both entrepreneurs and consumers who are directly involved in online transactions. The findings indicate that entrepreneurs perceive significant opportunities in online business, particularly in terms of broader market access, cost efficiency, and ease of transactions. However, they also face threats such as intense competition, data security issues, and dependence on technology that is vulnerable to disruptions. On the consumer side, the opportunities relate to convenience, easy access to products, and a wider variety of choices, while threats include concerns over product quality, the risk of fraud, and delivery issues. This research provides valuable insights for both entrepreneurs and consumers to identify strategies that can maximize the potential of online business while mitigating existing risks.